A preliminary experimental examination of worldview verification, perceived racism, and stress reactivity in African Americans. - Todd Lucas; Mark A. Lumley; John M. Flack; Rhiana Wegner; Jennifer Pierce; Stefan Goetz (2016)
According to worldview verification theory, inconsistencies between lived experiences and worldviews are psychologically threatening. These inconsistencies may be key determinants of stress processes that influence cardiovascular health disparities. This preliminary examination considers how experiencing injustice can affect perceived racism and biological stress reactivity among African Americans. Guided by worldview verification theory, it was hypothesized that responses to receiving an unfair outcome would be moderated by fairness of the accompanying decision process, and that this effect would further depend on the consistency of the decision process with preexisting justice beliefs.A sample of 118 healthy African American adults completed baseline measures of justice beliefs, followed by a laboratory-based social-evaluative stressor task. Two randomized fairness manipulations were implemented during the task: participants were given either high or low levels of distributive (outcome) and procedural (decision process) justice. Glucocorticoid (cortisol) and inflammatory (C-reactive protein) biological responses were measured in oral fluids, and attributions of racism were also measured.The hypothesized 3-way interaction was generally obtained. Among African Americans with a strong belief in justice, perceived racism, cortisol, and C-reactive protein responses to low distributive justice were higher when procedural justice was low. Among African Americans with a weak belief in justice however, these responses were higher when a low level of distributive justice was coupled with high procedural justice.Biological and psychological processes that contribute to cardiovascular health disparities are affected by consistency between individual-level and contextual justice factors. (PsycINFO Database Record